The Merchant of Venice - Shakespeare, William; Edited By W. Moelwyn Merchant (London Penguin Books, 1967)
he Merchant of Venice has been performed more often than any other comedy by Shakespeare. This edition pays special attention to the expectations of its first audience, and to our modern experience of seeing and hearing the play.
Keywords: Italy--Venice -- Merchant of Venice (Shakespeare, William)